ANALISIS KUALITAS LAYANAN PADA PERUSAHAAN JASA TRAVEL AGENT BERBASIS E-COMMERCE DENGAN METODE E-SERVQUAL DAN QUALITY FUNCTION DEPLOYMENT - Lithrone Laricha; Agung Saryatmo; Lita Avilla (Business Management Journal, 2017)
ABSTRACTInternet media used by individuals and companies for communication and business practice is known as e-commerce which recently has been growing rapidly in Indonesia, one of which is online travel agent. Therefore, this research is aimed to evaluate and improve the service quality of online travel agent company to determine appropriate strategics for achieving competitive advantages and increasing both customer loyalty and long-term profitability. Research data was obtained by reviewing literature and distributing questionnaires to appropriate respondents in Jakarta. The multiple linear regression generated the equation of Y=0,507+0,412X1+0,053X2-0,051X3 +0,048X4+0,134X5+0,184X6-0,038X7+0,096X8. Based on E-ServQual method, negative values obtained from 24-service attributes had not been in accordance with the customer expectation. Researcher obtained four attributes as improvement key-priorities by mapping each attributes into the IPA matrix. Meanwhile, by using Kano model for attributes categorization, researcher was able to derive eight attributes suitable in indifferent category, four attributes in must-be category, and twelve attributes in one-dimensional category. Finally, after integrating the results of E-ServQual and Kano model into QFD, researcher got the five technical responses with the largest percentage which is expected to better fulfill the customer desire and satisfaction.Keywords: Multiple Linear Regression Analysis, E-ServQual, Importance-Performance Analysis, Kano Model, Quality Function Deployment